Inflammatory Choroidal Neovascular Membranes: Clinical Profile, Treatment Effectiveness, and Visual Prognosis - Gonçalo Carrola; Mário Lima-Fontes; Fernando Falcão-Reis; Luís Figueira; Ângela Carneiro (Journal of Ophthalmology)
Purpose. To characterise a sample of patients with inflammatory choroidal neovascularization (I-CNV), including clinical profile, underlying aetiology and its course, treatments performed, associated clinical response, and visual prognosis. Methods. Retrospective analysis of patients with a diagnosis of I-CNV followed at the Ophthalmology Department of Centro Hospitalar Universitário de São João (CHUSJ). Clinical and visual outcomes were classified according to the difference in visual acuity after treatment. Results. Twenty eyes from 17 patients were analysed (11 female and 6 male patients, mean age 41.90 ± 16.457 years at CNV diagnosis). Punctate inner choroidopathy/multifocal choroiditis was the predominant inflammatory aetiology (10 patients, 58.82%). Median follow-up time was 46 months (range 10 to 188 months). Neovascularization was treated with intravitreal anti-VEGF injections (bevacizumab, aflibercept, and ranibizumab), and inflammation with anti-inflammatory/immunosuppressive therapy (oral, intravenous, and/or intravitreal corticosteroids; oral cyclosporine or methotrexate). Intravitreal anti-VEGF agents had a median number of 7.00 injections (IQR, 4.25 to 29.00). Visual acuity among 20 eyes had a mean gain of 15.10 ± 12.998 ETDRS letters after anti-VEGF treatment (p=0.000051). According to our classification, 16 had an improved outcome (80.00%), 3 had a stable outcome (15.00%), and 1 had a worsened visual outcome (5.00%). In addition, 13 eyes (65.00%) had a final VA equal to or greater than 65 letters. Recurrence was seen in 3 eyes (15.00%). Complications included cataract (6 patients) and ocular hypertension (4 patients). Conclusion. A combined approach with anti-VEGF agents and anti-inflammatory therapy was effective in I-CNV treatment, and an overall good visual prognosis was attainable. Intensive follow-up was fundamental in the management of both the primary inflammatory and secondary neovascular conditions.